COMPOSITION-INDUCED SUPERCONDUCTIVITY (UP TO 55-K) IN THE SYSTEM (PB0.75CU0.25)SR2(CA1-XYX)CU2O7-DELTA - Liu, R; Hu, S; Gameson, I; Edwards, P; Maignan, A; Rouillon, T; Groult, D; Raveau, B (1991)
We demonstrate a compositionally induced superconductor-to-semiconductor transition in the system (Pb0.75Cu0.25)Sr2(Ca1-xYx)Cu2O7-δ. Superconducting behavior is observed over the composition range 0.1 ≤ x ≤ 0.6. Samples with 0.1 ≤ x ≤ 0.3 are multiphasic, but the superconducting transition temperature is a maximum (55 K) over this range of compositions. The sample having x = 0.5 gives rise to an acceptable phase purity, a superconducting transition temperature of 45 K, and the maximum superconducting (Meissner) volume fraction (20.2%). A superconductor-to-semiconductor transition occurs at x = 0.7. © 1991 Academic Press, Inc.